Computing concepts - Haag, Stephen (McGraw-Hill Technology Education, 2004)
This exciting and innovating concepts text emphasizes all that is current, cutting-edge, and interesting to students in the introductory course. Focusing specifically on users, consumers and purchasers of technology, this text provides a no-nonsense coverage of the absolute essentials for using technology in today's wired (and wireless!) world. The "I-Series" offers excellent coverage of the basics, as well as extensive information on building a Web site, E-Commerce, implications of technological advances, buying your first PC, maintaining a computer system, and more. Each chapter also contains coverage of ethics, security, and privacy.